Pengaruh Self-Efficacy Terhadap Perilaku Keuangan Mahasiswa - Anggono, Anggono; Barus , Alexander; Nasution, Siti Aisyah; Astuty, Fuji; Tarwiyah (Politeknik Ganesha Medan, 2024)
The problem examined in this research is the uncontrolled financial behavior of students. The purpose of this study was to examine the differences in financial behavior of students with high, moderate, and low self-efficacy and to examine the effect of self-efficacy on student financial behavior. The population of this research consisted of 150 students. The sampling technique used in this research was simple random sampling, so the research sample consisted of 109 students. The type of research used is quantitative research. The research method used is ex post facto (causal-comparative). The data collection technique used is a questionnaire. Data analysis techniques used are descriptive statistics, pre-requisite tests consisting of normality tests, homogeneity tests, and inferential statistics such as one-way ANOVA and further tests. This research produced four research results. First, there are significant differences in students' financial behavior with low, moderate, and high self-efficacy. Second, students with moderate self-efficacy have higher financial behavior than those with low self-efficacy. Third, students with high self-efficacy have higher financial behavior than those with low self-efficacy. Fourth, students with high self-efficacy have higher financial behavior than those with moderate self-efficacy. This research concludes that self-efficacy positively and significantly affects student financial behavior.